Auta de Souza, a poeta de pele clara, um moreno doce : memória e cultura da intelectualidade afrodescendente no Rio Grande do Norte - Farias, Genilson de Azevedo (2013)
In the first half of the twentieth century different groups of intellectuals were engaged in the pursuit of an ideal of Brazility. Thereon, two currents are perceived. The first was marked by a nostalgic bias about the past, being formulated by intellectuals from the region that was turning as Northeast. This group of intellectuals emphasized values and traditions of the agrarian aristocracy of the region that was losing visibility in the political and economic Brazil scene. Already the other current has a more modern and industrial feature, was formed by intellectuals from the Southeast that in detriment of the first, was rising. This group, on the other hand, was intended to give a new face to Brazil and break with the "roots" of our delay that in their view were linked to our agrarian past. This resulted in different perceptions and interpretations of our historical past, and the construction of different profiles to the Brazilian. Accordingly, our work seeks to understand how was produced the writing that silenced the mixed ancestry of Auta de Souza (1876-1901) considering the position that she should occupy in the intellectuals projects who were in charge of forming a memory for our state. Auta as a relevant historical character in this project of potiguares intellectuals, she was raised to the condition of a model woman and elected in the pantheon of the most beloved poets of Rio Grande do Norte, however, to occupy such prestigious position she had her racial ancestry concealed in the writings that these same intellectuals had written about her, what is still spreaded in memory and rituals places of religious and civic features